2020
DOI: 10.1021/acs.nanolett.0c01356
|View full text |Cite
|
Sign up to set email alerts
|

Type-II Ising Superconductivity and Anomalous Metallic State in Macro-Size Ambient-Stable Ultrathin Crystalline Films

Abstract: Recent emergence of two-dimensional (2D) crystalline superconductors has provided a promising platform to investigate novel quantum physics and potential applications. To reveal essential quantum phenomena therein, ultralow temperature transport investigation on high-quality ultrathin superconducting films is critically required, although it has been quite challenging experimentally. Here, we report a systematic transport study on the ultrathin crystalline PdTe 2 films grown by molecular beam epitaxy (MBE). In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 37 publications
(60 reference statements)
4
57
0
Order By: Relevance
“…In fact, there exists not just one type-II Ising superconductor. In ultrathin PdTe 2 grown by MBE, Liu et al [22] observed largely enhanced B c2,∥ , exceeding B p by a factor of 6-8 (Fig. 2d).…”
Section: Discovery Of Ising Superconductorsmentioning
confidence: 84%
See 1 more Smart Citation
“…In fact, there exists not just one type-II Ising superconductor. In ultrathin PdTe 2 grown by MBE, Liu et al [22] observed largely enhanced B c2,∥ , exceeding B p by a factor of 6-8 (Fig. 2d).…”
Section: Discovery Of Ising Superconductorsmentioning
confidence: 84%
“…Black: spinorbit coupling (SOC) related systems[45,47], Blue: Type-I Ising superconducting materials[5, 12, 14- 16, 18, 74]. Red: Type-II Ising superconducting materials[21,22]. Orange: "beyond" Ising-type superconductivity[50][51][52]72].…”
mentioning
confidence: 99%
“…Very recently, anomalous metallic state was also observed in MBE‐grown PdTe 2 thin films under a perpendicular magnetic field; the detection was convincing since more than 99.999% of high‐frequency noise power was reduced by the high‐quality filter. [ 125 ] In conclusion, the quantum metallic state has brought wide interest and whether the quantum metallic state is an intrinsic state has fundamental importance for us to understand the quantum material and quantum phase transitions.…”
Section: Bcs Superconductorsmentioning
confidence: 99%
“…Similar type‐II Ising superconductivity was also discovered in the centrosymmetric MBE‐grown ultrathin PdTe 2 films very recently, where the in‐plane critical field is more than 7 times of the Pauli limit. [ 125 ] In the type‐II Ising superconductors, the Ising‐like pairing occurs between the carriers around Γ‐point with their spins aligned perpendicular to the plane rather than the K and K′ points observed in 2H‐type MoS 2 and NbSe 2 , and more type‐II Ising superconductors are expected in the future discovery. [ 254 ]…”
Section: Robust 2d Superconductormentioning
confidence: 99%
“…Since stronger inversion symmetry breaking attribute to the missing up-turn feature, a pentalayer stanene should experience a weaker Rashba effect, giving rise to an apparent enhancement of B c;== at low T. This indicates a broader range of inversion symmetry materials host such pairing mechanisms. Recent experiment in ultra-thin crystalline PdTe2 films also demonstrates clear feature of type-II Ising pairing with in-plane critical field more than 7 times the Pauli limit [67].…”
Section: Type-ii Ising Superconductormentioning
confidence: 94%